Monitoramento em tempo real da cristalização quiescente e induzida por fluxo de polipropileno em microscópio óptico de luz polarizada - Berl, Johann Henrique (2015)
In the polymer forming processes, such as injection molding, extrusion of films / sheets and blowing, these materials are subject to shearing and elongation flows. Such conditions influence its final morphologies. When rapid crystallization polymers are injection molded at high shear rates typical morphology exhibit skin-core highly oriented: outer layers and spherulitic cores. The outer layer or skin, crystallization occurs under the influence of flow and it is known as flow-induced crystallization (CIF). This work improved methodology from literature (Spruiell et al) of real-time monitoring of quiescent crystallization kinetics under isothermal and non-isothermal conditions, in addition the evaluation of induced flow crystallization at low shear rates. This study done with conducted to iPP using an optical microscope with polarized light completed with a shear cell and reo-optical signals, in which stimuli in the visible region was applied, which allowed verification of birefringence and scattering light phenomena simultaneously capture images during the crystallization process, for that an accessory using LDR has been developed. The method was compared to the kinetics of crystallization in the differential scanning calorimeter. At the isothermal quiescent crystallization condition six different temperatures were evaluated and it was found that higher temperatures favored for lower growth rates. In non-isothermal quiescent conditions, was found that for higher cooling rates the crystallization induction time was reduced. By applying different shear rates at isothermal conditions, it was found that the increase in shear rate reduced the polymer's crystallization induction time, indicating the influence of the orientation of the polymer chains and increasing the number of crystallization nuclei. The results showed that this methodology has applicability and good quantitative performance; thus the methodology developed could be used for futures analysis of quiescent and shear-induced kinetics crystallization process with real time reo-optical signals.